Enhanced handoff latency reduction mechanism in layer 2 and layer 3 of mobile IPv6 (MIPv6) network - Anwar, Farhat; Masud, M. H.; Bari, S.M. Sadakatul; Abd Latif, Suhaimi (INSI Publications, 2013)
Next Generation Networks (NGN) both static and mobile are expected to be fully Internet Protocol Version 6 (IPv6) based. Mobility in IPv6 (MIPv6) network was designed to provide Internet services to end users at anytime and anywhere. However, MIPv6 is not widely deployed yet due to handoff latency and other limitations leading to packet loss and Quality of Service (QoS) degradation for real time applications such as audio and video streaming. MIPv6 handoff latency can be categorized into layer 2 (L2) and layer 3 (L3) delays that includes link layer establishment delay, movement detection delay, address configuration delay and binding update or registration delay. Movement detection delay and address configuration including Duplicate Address Detection (DAD) in L2 and L3 respectively consume the highest time of the total delay. In order to reduce these handoff latencies, two solutions are proposed to focus all the delays both in L2 and L3. The first solution is the fuzzy logic technique based network awareness to reduce movement detection delay especially the scanning time in L2 in heterogeneous networks. The second solution is Parallel DAD (PDAD) to reduce address configuration time in L3. Both solutions benchmarked with OMNeT++ simulator show improvements over standard MIPv6 networks. The handoff latency reduced more than 50% and packet loss improved around 55% in L2. Moreover, in L3 the handoff latency reduction accounts for 70% and packet loss improved approximately 60%. The handoff latency is reduced from 1300 ms to 500 ms applying fuzzy logic technique at L2 and PDAD mechanism in L3 leading to overall delay reduction of 60%.